El miedo al viaje: un estado de la cuestión - Korstanje, Maximiliano (Nómadas. Critical Journal of Social and Juridical Science, 2008)
Phobias have been studied broadly from a pathological perspective as a paralyzing fear regarding specific objects or situations. Nevertheless, not only in Greek language phobia means just fear but also should be tackled off from a new posture than clinical. Paradoxically, in recent years the cases of persons who manifested a phobia episode of flying or travelling have been multiplied elsewhere in spite of all technological advantages. For that reason, the following theoretical essay is aimed at setting certain initial hypothesis to be continued in empirical works for further understanding.
Keywords: Tourism; Journey; Fear; Social psychology; Secure base theory